Polar nano-region structure in the oxynitride perovskite LaTiO2N. Issue 9 (8th January 2020) - Yamaura, Jun-ichi; Maki, Sachiko; Honda, Takashi; Matsui, Yoshio; Noviyanto, Alfian; Otomo, Toshiya; Abe, Hitoshi; Murakami, Youichi; Ohashi, Naoki
Abstract : Polar nano-region formation in the oxynitride perovskite LaTiO2 N is demonstrated from PDF analysis. Abstract : We investigated the multiscale characters of the crystal structure of the oxynitride perovskite LaTiO2 N. While X-ray diffraction results identified the average structure as being centrosymmetric, we detected a signature of unknown structural deformation. By viewing the local structure, we unveiled the formation of a polar structure at the nanoscale.